Negative circular polarization dynamics in InP/InGaP quantum dots. (August 2016) - Nekrasov, S V; Kusrayev, Yu G; Akimov, I A; Korenev, V L; Langer, L; Salewski, M
Abstract: Photoluminescence (PL) negative circular polarization (NCP) dynamics of InP/InGaP quantum dots (QDs) was studied. Time resolved measurements of PL demonstrated that NCP vanishes, when transverse magnetic field is applied, while oscillations of polarization (that are typical for both low-dimensional and bulk materials) do not occur. Hole g-factor spread in the QD ensemble was supposed to be the most probable reason for such NCP magnetic field behavior. The dependence of NCP dynamics on the repetition period of excitation laser pulses was investigated. In case of fairly small repetition period (T = 13.3 ns) long living NCP (13.3 ns < t < 133 ns) was detected, what was ascribed to resident electron spin orientation, accumulated during many laser pulses. In that regime more than one luminescence polarization decay time exist.